Active Surveillance of Adverse Events with Particular Interest Following Vaccination Against COVID-19 in Burkina Faso - KA, Zoungrana; D, Koala; M, Bountogo; I, Ouédraogo; R, Yougbaré; TR, Ouédraogo; R, Diao; R, Sana; C, Gourmanon; A, Agawa; M, Rychen; K, Ahawo; et al. (Archives of Clinical and Biomedical Research, 2025)
Introduction: Coronavirus 2019 or COVID-19 disease caused by SARSCoV- 2 first emerged in Wuhan, China. In Africa, there were 8,580,381 confirmed cases at the end of March 2022. Burkina Faso had 20,858 confirmed cases and 382 deaths in April 2022. Like other countries, vaccination is used as the main means of disease control. Rumors of vaccination-related side effects limit its uptake. This study aims to evaluate the safety of COVID-19 vaccines among vaccinated people in Burkina Faso. Methodology: This study was a prospective cross-sectional study. It consisted of active surveillance of the safety of 3 anti-COVID-19 vaccines: Ad26.COV2. S vaccine, the BNT162b2 vaccine and the BBIBP-CorV vaccine. A total of 355 participants were included for each of the 3 vaccine types. These participants after informed consent received the vaccines and were monitored by telephone and/or home visit for 84 days. Results: A total of 1329 participants were included, and between 77.2% and 100% of them were followed up for 84 days by vaccine type. The vast majority of adverse events were reported at Day1 after vaccination. Local adverse events were observed with the 3 types of vaccine. They were 11.6% (95% CI 9.1 ; 14.7), 4.9% (95% CI=3.3 ; 7.4) and 2.9% (95% CI 1.7 ; 5.2) respectively for Ad26.COV2. S Vaccine, BNT162b2 Vaccine and BBIBPCorV Vaccine respectively. Systemic adverse events were reported at 10% [95% CI 7.7 ; 13] for Ad26.COV2. S vaccine, 6.3% [95% CI 4.4 ; 8.9] for BNT162b2 vaccine and 3.5% [95% CI 2.0 ; 5.8] for BBIBP-CorV vaccine. With the BNT162b2 vaccine, women are 2.7 times likely to develop (95% CI = 1.1 - 6.5) more adverse events than men. No serious adverse events were reported. Conclusion: The results obtained are similar to those of other approved vaccines used in routine immunization. The adverse events reported were transient. Adverse events were more frequently reported in women than in men, and generally lasted one to two days after vaccine administration. The essential limitation of this study was self-reporting by participants. The data were used on a daily basis to increase awareness and uptake of COVID-19 vaccination. The probability of occurrence and type of adverse events were key messages at follow-up.